2018
DOI: 10.15835/nbha46110941
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Potential of Velvet Bean against Rigid Ryegrass

Abstract: Environmental concerns and several adverse effects of reliance on and improper use of pesticides make necessary the use of alternative methods. Allelopathy has a rather unexploited potential in integrated weed management and ought to be further studied. The allelopathic effects of velvet bean (Mucuna pruriens (L.) DC. var. utilis) on seedling emergence and first growth of the important weed rigid ryegrass (Lolium rigidum L.) were evaluated in a pot experiment conducted at Agricultural University of Athens. Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…var. utilis) has allelopathic potential and can help to reduce rigid ryegrass biomass, height, and leaf number [153] * All diversification strategies were used in combination with a suitable herbicide program.…”
Section: Crop Rotationmentioning
confidence: 99%
“…var. utilis) has allelopathic potential and can help to reduce rigid ryegrass biomass, height, and leaf number [153] * All diversification strategies were used in combination with a suitable herbicide program.…”
Section: Crop Rotationmentioning
confidence: 99%
“…Methyl cinnamate can also significantly reduce L. rigidum seed germination and root length when applied at 640 nL cm -3 (Vasilakoglou et al, 2013). Given that L. rigidum is a noxious weed species infesting cereal crops with remarkable ability to evolve multiple herbicide patterns to up to 14 different modes of action, the use of allelochemical extracts from plants pose as an alternative and attractive option for its control (Adler and Chase, 2007;Heap, 2014;Travlos et al, 2018).…”
Section: Allelopathic Effects Of Acacia Dealbata Link On Weedsmentioning
confidence: 99%
“…Yoshiharu (2003) reported that incorporation of fresh leaves of Mucuna pruriens into the soil (1.0%) w/w in dry weight equivalent reduced succeeding emergence of Phaseolus vulgaris up to 60% and plant biomass up to 30% of the control. Travlos et al (2018) similarly reported that velvet bean's residues reduced height, leaf number and biomass of rigid ryegrass up to 26, 51 and 62%, respectively. L-DOPA inhibited the growth of some companion plants, and that it probably contributed to its allelopathy.…”
Section: Introductionmentioning
confidence: 84%
“…Mucuna stover produced two terpenoids and four phenols but similar compounds had not been reported in literature. L-DOPA, a phenolic compound was reported as the dominant compound in mucuna vegetative parts (Vadivel & Pugalethi, 2008;Travlos et al, 2018). Mucuna stover was observed to reduce root growth of lettuce seedlings by Tomita (2003).…”
Section: Discussionmentioning
confidence: 99%